5(4+m)-3(3m-1)=-9

Simple and best practice solution for 5(4+m)-3(3m-1)=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(4+m)-3(3m-1)=-9 equation:


Simplifying
5(4 + m) + -3(3m + -1) = -9
(4 * 5 + m * 5) + -3(3m + -1) = -9
(20 + 5m) + -3(3m + -1) = -9

Reorder the terms:
20 + 5m + -3(-1 + 3m) = -9
20 + 5m + (-1 * -3 + 3m * -3) = -9
20 + 5m + (3 + -9m) = -9

Reorder the terms:
20 + 3 + 5m + -9m = -9

Combine like terms: 20 + 3 = 23
23 + 5m + -9m = -9

Combine like terms: 5m + -9m = -4m
23 + -4m = -9

Solving
23 + -4m = -9

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -4m = -9 + -23

Combine like terms: 23 + -23 = 0
0 + -4m = -9 + -23
-4m = -9 + -23

Combine like terms: -9 + -23 = -32
-4m = -32

Divide each side by '-4'.
m = 8

Simplifying
m = 8

See similar equations:

| 3a+10=3a-4 | | 9ab^2+27a^3-27a^2b-b^3+c^3=0 | | 2z+6=36 | | 5p+9=4p+8 | | -2(6z-3)+13(z-7)=-81-9 | | 25x=4x^(1/3) | | 9s-8(s-10)+3=84 | | 3x+8y=59 | | -3(s-2)+4s=-11-2 | | 7(s-2)+4s=-11-2 | | 5(3x+8)+5x=5(2d+10)-36 | | 4(4b+6)=3(2b-18) | | y=150-s | | 4(3y-1)-2y=56 | | 3(2n-6)=4m-10 | | 9(m-1/3)=9 | | 13=145-11q | | 20=90-5q | | (y+2)-2(y+3)=4(x+1) | | 19=55-4p | | 12p+14=86 | | 111-9p=12 | | 5(x+2)-2(x+3)=4(x+1) | | 17=39-2p | | 6=72-11q | | 5y+6y-81=7x+102+65y | | 12q+9=81 | | 8=56-4x | | 13=58-5q | | 8q-35=61 | | 21=48-9q | | 53=6p+11 |

Equations solver categories